An Ethical Analysis of Human Cerebral Organoids - Bin HUANG (Yixue yu zhexue)
Human cerebral organoids are three-dimensional neural tissues with similar structure and biological function to human brain. Human cerebral organoids can be used to study human brain development, disease mechanisms, and drug screening. However, in vitro human cerebral organoids have the risk of consciousness, moral status and informed consent issues, and face ownership issues and conflicts with neurodiversity values in applications. The ethical risks faced by human cerebral organoid chimera include its welfare, consciousness and moral status, as well as human dignity and moral humanization. The integration of human cerebral organoids with artificial intelligence or other types of organoids leads to the emergence of complex multi-brain organoid composites. The moral status and autonomy of such composites are expected to become focal points in future research.